'Picture me healthy': a pilot study using photovoice to explore health perceptions among migrant youth in Beijing, China. (September 2017) - Leung, May May; Jun, Jing; Tseng, Anna; Bentley, Margaret
Globalization has resulted in an influx of migrant families from rural provinces into the urban areas of China. Although the migrant population may live in the same cities as urban residents, they experience different lives because of restricted access to job opportunities, social services, and schools for children. Limited research exists with Chinese rural-to-urban migrant youth, particularly using community-based approaches. This study explored migrant youths' perceptions of their nutrition, physical activity, and health environment, using the community-based participatory research method of photovoice. Twelve migrant youth (6 boys and 6 girls) in Beijing, China, participated in two photovoice assignments focused on personal safety, nutrition, and physical activity. The photographs taken by the youth guided group discussions and semi-structured interviews. Inductive and deductive processes were used to identify codes (ideas emerging from text); similar codes were grouped into themes. Pedestrian safety was the most common personal safety concern. Another safety issue was the excess garbage in the community. Garbage was also a barrier to nutrition and physical activity as it was a food sanitation concern and limited the physical environments where children could play. Schools and community recreation centers were perceived as facilitators of physical activity. However, community centers were also a barrier as a limited number of them caused overcrowding, resulting in safety concerns. Photovoice enables youth to express their health perceptions. Our data provide interesting preliminary insight into the lives of Chinese migrant youth, which could help inform the development of interventions and advocate for positive environmental changes for this marginalized population.